Augmented Reality Sebagai Media Edukasi Interaktif Untuk Mengenali Jenis Ikan Konsumsi Pada Siswa Sekolah Dasar - Cindy Asyra Fratari; Shinta Puspasari; Lastri Widya Astuti (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to develop an interactive learning media using Augmented Reality (AR) to support the introduction of edible fish species for fourth-grade students at SD MIS Adabiyah 02 Palembang. The media is designed to provide an engaging and enjoyable learning experience through the use of marker-based AR technology that can be operated on Android Devices. Fish objects are visualized in three-dimensional (3D) form, allowing students to view and interact with them directly through the camera.The development method used in this study is the Rational Unified Proxess (RUP), which consist of four phases: inception, elaboration, construction, and transition. The design process involves 3D object modelling using Blender 3D and AR integration through Unity and Vuforia SDK. The results of this study are expected to help students better understand the material related to various type of edible fish. The usability using the System Usability Scale (SUS) resulted in an average score of 90 from 31 respondetns, indicating that the appliacation has an excellent level of usability and feasibility.